The Book of Revelation: a biography - Beal, Timothy K. (Lives of Great Religious Books, 2018)
Frontmatter -- Contents -- Preface -- Chapter 1. Introduction -- Chapter 2. Pale Rider: Obscure Origins -- Chapter 3. Apocalypse Not Now: Augustine's Tale of Two Cities -- Chapter 4. Cry Out and Write: Hildegard's Apocalypse -- Chapter 5. Mind's Eye: Joachim in the Forests of History -- Chapter 6. September's Testament: Luther's Bible vs. Cranach's Revelation -- Chapter 7. New World of Gods and Monsters: Othering Other Religions -- Chapter 8. Heaven in a Garage: James Hampton's Throne Room -- Chapter 9. Left Behind, Again: The Rise and Fall of Evangelical Rapture Horror Culture -- Chapter 10. Post Script: Revelation Becomes Us -- Further Reading -- Acknowledgments -- Notes -- Index